2015
DOI: 10.1590/1678-476620151054453460
|View full text |Cite
|
Sign up to set email alerts
|

Nest site selection by Hypsiboas faber(Anura, Hylidae) in Southern Brazil

Abstract: ABSTRACT. Male gladiator frogs of Hypsiboas Wagler, 1830 build nests on available substrate surrounding ponds and streams where female spawn eggs during the breeding period. Although gladiator frogs seem to show plasticity in the way they construct their nests, there is no study reporting if these species present preferences about microhabitat conditions for nest-building (mainly under subtropical climate). Predation pressure and environmental conditions have been considered major processes shaping the great d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A visible frog foam nest increases a male's chances of mating [ 177 ] and nest building during mating arguably allows females to choose direct benefits through protection of the offspring from predation and desiccation [ 178 ]. Other types of male nests found among frogs are burrows [ 179 ] and water-filled bowls [ 180 , 181 ]. Although vocalization is a major part of male courtship, nest shape and location [ 177 , 179 , 180 ], as well as nest building per se [ 178 ], may be targets of female choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A visible frog foam nest increases a male's chances of mating [ 177 ] and nest building during mating arguably allows females to choose direct benefits through protection of the offspring from predation and desiccation [ 178 ]. Other types of male nests found among frogs are burrows [ 179 ] and water-filled bowls [ 180 , 181 ]. Although vocalization is a major part of male courtship, nest shape and location [ 177 , 179 , 180 ], as well as nest building per se [ 178 ], may be targets of female choice.…”
Section: Discussionmentioning
confidence: 99%
“…Other types of male nests found among frogs are burrows [179] and water-filled bowls [180,181]. Although vocalization is a major part of male courtship, nest shape and location [177,179,180], as well as nest building per se [178], may be targets of female choice. All examples mentioned so far are species with external fertilization.…”
Section: (C) Choosiness and Preference For Nest Traitsmentioning
confidence: 99%
“…According to Murphy (2003), the temperature of the reproduction sites possesses a great influence on the behavior of adult anurans, which can choose places for oviposition with conditions more appropriate for a species' embryonic-larval development. Luza et al (2015) have also shown that adult Boana faber (Wied-Neuwied, 1821) are able to select nesting sites in shallow waters with few organic particles in suspension and more covering provided by surrounding vegetation, providing developing larvae microhabitat conditions significantly different from a randomly chosen nesting site. Additionally, specifically chosen nesting sites may provide favorable microclimates that could accelerate larval development, when the nest containing eggs or larvae heats up more rapidly in sunlight than the surroundings (Dobkin and Gettinger 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of nidification behavior usually focus on the most common foam nest type that occurs in many arboreal species ( Limnodynastes peronii , Rhacophorus spp., etc.) 18 , 19 , while mud nests are relatively overlooked as it has only been documented in a few lentic species, such as Boana faber 20 , Limnonectes limborgi 21 , and some species of Nidirana 22 .…”
Section: Introductionmentioning
confidence: 99%